Membangun Kesadaran Siswa dengan Menanam dan Memasak Sayuran dari Rempah-Rempah Alami di SMP Paramarta Tangerang Selatan - Munawir, Abdillah; Rusdiyanto, Edi; Sumartono, Sumartono; Putri, Erika Pradana; Muna, Siti Umamah Naili (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
The school students and teachers are national assets, they are given priority when it comes to community service projects that emphasize teaching about organic vegetable growing and using natural spices in cooking to benefit kids' and instructors' health. The method used is Active and Participatory Learning, emphasizing discussion, practice, and demonstration. The results of this service have added to the understanding of students and teachers by planting organic vegetables and cooking vegetable ingredients using natural spices. It has successfully instructed pupils from a young age on how to maintain health by eating organic vegetables and herbs and carrying out the most basic tasks, such as growing plants. Vertical organic vegetables, then practice cooking with spices. The decision to adopt this viticulture planting method was made since only a small 2.5 x 4 m plot of land can be used to grow organic vegetables with the highest yields. The viticulture method itself can produce a lovely environment and economic significance. To treat students and create a relaxing and comfortable atmosphere in the classroom (i). Besides that, using vegetable cooking techniques can increase students' understanding of knowing natural spices that can be used as cooking spices that guarantee the long-term health of students and teachers.